Responding to stigmatization: How to resist and overcome the stigma of unemployment. Issue 10 (October 2022) - Garcia-Lorenzo, Lucia; Sell-Trujillo, Lucia; Donnelly, Paul
Organization research on stigma has mostly focused on the stigmatized, limiting the scope for exploring what is possible and lacking recognition of the structural conditions and unequal power relations that create and sustain stigma. Consequently, it overlooks how actors can organize to resist and potentially overcome stigmatization altogether. Addressing this question empirically, we studied the long-term unemployed in Spain using a longitudinal qualitative research design. We develop a typology of responses to stigmatization – getting stuck, getting by, getting out, getting back at and getting organized – that advances our understanding of stigma in several ways. First, our typology captures stigma as a multilevel phenomenon. Second, it makes explicit that stigma can only be understood in relation to its socio-historical contexts and unequal relations of power. Third, it captures how resisting stigma needs to be a collective enterprise and advances the importance of organizing to both challenge stigmatization and explore alternatives.